IMPLEMENTASI KURIKULUM AL-ISLAM, KEMUHAMMADIYAHAN DAN BAHASA ARAB DALAM MENINGKATKAN AKHLAK SISWA DI SMK MUHAMMADIYAH KARANGMOJO - Osa Agil Pratama; Hendro Widodo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
ABSTRACTThe purpose of this study was to describe the Implementation of theKemuhammadiyahan Al-Islam Curriculum and Arabic Language and the moralimprovement of students at the Muhammadiyah Vocational School Karangmojo. Thisresearch is a type of qualitative research. The location of the research was conducted atthe Muhammadiyah Vocational School of Karangmojo Gunungkidul. Data collectiontechniques using in-depth interviews, documentation and observation. Data analysismethods include 3 stages, namely data reduction, data presentation, and drawingconclusions with verification. The results showed that the implementation of theKemuhammadiyahan Al-Islam Curriculum and Arabic Language had largely met theCurriculum Implementation Standards. The disadvantages of learning evaluation arestill focused on aspects of knowledge, while aspects of attitudes and skills still lackattention. The moral level based on observations of researchers has shown an increase.Keywords : Implementation of Curriculum, ISMUBA, Morals